2007
DOI: 10.1080/13102818.2007.10817422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Energy on Fungal Growth of Resilient Denture Liner Material

Abstract: Contamination of resilient denture liner material with microorganisms, particularly Candida albicans, is a common clinical problem. Denture hygiene is essential to maintain the serviceability of the denture, and microwave has been suggested for denture disinfection. A resilient denture liner material was contaminated with Candida albicans and reduction of organism counts after test disinfection methods (microwave energy, soaking overnight in a dilute sodium hypochlorite and alkaline peroxide solutions) calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…This was attributed to biofilm formation, as C. albicans nullified the toxic effect of sodium perborate and survived even after 5 min of exposure. This agreed with the findings of the previous studies by Dills et al and Drake et al [32,38]. They both identified that alkaline peroxide denture cleansers are effective against the streptococcus species and do not show much activity against C. albicans.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was attributed to biofilm formation, as C. albicans nullified the toxic effect of sodium perborate and survived even after 5 min of exposure. This agreed with the findings of the previous studies by Dills et al and Drake et al [32,38]. They both identified that alkaline peroxide denture cleansers are effective against the streptococcus species and do not show much activity against C. albicans.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that microwave-disinfected samples displayed a significantly decreased CFU count of C. albicans at 3 min of exposure. Previous studies revealed that microwave disinfection initiates a change in the structure and permeability of the fungal cells, resulting in alterations in cell metabolism, causing cell death [32][33][34]. These results agree with the outcomes of the study conducted by Al-Saadi et al [28].…”
Section: Discussionsupporting
confidence: 90%
“…Because of that the most effective preventive and curative treatment for pathogens is believed, denture cleansers have been studied to identify the ideal product. (10) Dentures can be cleaned mechanically, chemically or through a combination of these. (11) Chlorhexidine gluconate is a cationic oral antiseptic agent with bactericidal activity and acts by destabilizing and penetrating in bacterial cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, using an unmodified domestic microwave oven with a rotating table, Baysan et al (1998) observed that microwave irradiation at 650W for 5 minutes promoted a reduction in the quantity of C. albicans and S. aureus present in resilient relining materials. The study of Meşe & Meşe (2007) also investigated the effect of microwave energy on the growth of C. albicans in resilient relining material and verified the reduction in the colony counts of the fungus after dry exposure to microwaves for 5 minutes (650W). The results obtained with the aforementioned microbiological studies, in which the test specimens or dentures were irradiated in a dry state, are variable with regard to the effectiveness of disinfection by microwaves.…”
Section: Microbiological Effectiveness and Recommended Protocolsmentioning
confidence: 99%